Analysis on performance of borehole heat exchanger in a layered subsurface - Luo, Jin; Bayer, Manfred; Prieß, Anna; Xiang, Wei; Rohn, Joachim (Applied Energy, 2014)
Keywords: Borehole heat exchanger (BHE); Ground properties; Ground source heat pump (GSHP) system; Layered subsurface; Numerical model

Determination of ground thermal properties for energy piles by thermal response tests - Luo, Jin; Zhao, Haifeng; Huang, Wei; Zhu, Yongqiang; Xiang, Wei; Rohn, Joachim (Environmental Earth Sciences, 2018)
Keywords: Effective thermal conductivity; Energy pile; Borehole thermal resistance; Ground heat exchanger

Heating and cooling performance analysis of a ground source heat pump system in Southern Germany - Luo, Jin; Bayer, Manfred; Prieß, Anna; Wilkmann, Lucas; Xiang, Wei; Rohn, Joachim (Geothermics, 2015)
Keywords: Coefficient of performance (COP); Energy efficiency ratio (EER); Ground source heat pump (GSHP) system; System performance

Modeling and experiments on energy loss in horizontal connecting pipe of vertical ground source heat pump system - Luo, Jin; Bayer, Manfred; Prieß, Anna; Rohn, Joachim (Applied Thermal Engineering, 2013)
Keywords: Energy loss; Ground source heat pump system; Horizontal connecting pipe; Pipe burial depth Heat carrier fluid; Pipe insulation

Study on operation management of borehole heat exchangers for a large-scale hybrid ground source heat pump system in China - Luo, Jin; Zhao, Haifeng; Jia, Jia; Wei, Xiang; Rohn, Joachim; Blum, Philipp (Energy, 2017)
For large-scale Ground Source Heat Pump (GSHP) systems, the numerous Borehole Heat Exchangers (BHEs) are generally managed in units. The simultaneous operation of BHEs consume huge amount of energy by operating water-circulating-pumps. However, such an operation condition may waste energy when no peak thermal load is needed. Hence, operation management should be optimized according to timely energy demand to ensure efficient performance with minimum maintenance. In this paper, three operation conditions for a cooling load dominated GSHP system in China are studied. First, specific ground conditions of the BHE field are investigated. The GSHP system operation under intermittent heating and cooling conditions is simulated by Thermal Performance Test (TPT). In order to examine performance of the BHEs and ground temperature migration, a numerical heat transport model is developed. Modeling results indicate similar thermal performance of BHEs and ground temperature disturbance among the three operation alternatives over a 25-year period. Finally, economic performance and operating savings are analyzed. The optimized operation condition in which the operating numbers of BHEs was designed with monthly energy demand of the building could save around 25,000 CNY (∼3000 EUR) annually. © 2017 Elsevier L
Keywords: Energy management; Heat exchangers; Heat pump systems; Pumps; Borehole heat exchangers; Economic performance; Intermittent heating; Minimum maintenances; Operation conditions; Simultaneous operation; Thermal Performance; Water circulating pumps; Geothermal heat pumps; borehole; cooling; fuel consumption; ground conditions; heat transfer; heating; optimization; performance assessment; China

Thermal efficiency comparison of borehole heat exchangers with different drillhole diameters - Luo, Jin; Bayer, Manfred; Prieß, Anna; Rohn, Joachim (Energies, 2013)
Keywords: Borehole Heat Exchanger; Drillhole Diameter; Ground Source Heat Pump System; Thermal Efficiency

Thermal performance and economic evaluation of double U-tube borehole heat exchanger with three different borehole diameters - Luo, Jin; Bayer, Manfred; Prieß, Anna; Rohn, Joachim (Energy and Buildings, 2013)
Keywords: Borehole diameter; Borehole heat exchanger; Economic profitability; Ground source heat pump system; Saving-to-investment ratio (SIR); Thermal performance